Small molecule-based immunomodulators for cancer therapy - Yinrong Wu; Zichao Yang; Kui Cheng; Huichang Bi; Jianjun Chen (Elsevier, 2022)
Immunotherapy has led to a paradigm shift in the treatment of cancer. Current cancer immunotherapies are mostly antibody-based, thus possessing advantages in regard to pharmacodynamics (e.g., specificity and efficacy). However, they have limitations in terms of pharmacokinetics including long half-lives, poor tissue/tumor penetration, and little/no oral bioavailability. In addition, therapeutic antibodies are immunogenic, thus may cause unwanted adverse effects. Therefore, researchers have shifted their efforts towards the development of small molecule-based cancer immunotherapy, as small molecules may overcome the above disadvantages associated with antibodies. Further, small molecule-based immunomodulators and therapeutic antibodies are complementary modalities for cancer treatment, and may be combined to elicit synergistic effects. Recent years have witnessed the rapid development of small molecule-based cancer immunotherapy. In this review, we describe the current progress in small molecule-based immunomodulators (inhibitors/agonists/degraders) for cancer therapy, including those targeting PD-1/PD-L1, chemokine receptors, stimulator of interferon genes (STING), Toll-like receptor (TLR), etc. The tumorigenesis mechanism of various targets and their respective modulators that have entered clinical trials are also summarized.